Some methods for transforming sequential processes into concurrent ones - Thanh, Hoang Chi (VNU Journal of Science: Mathematics - Physics, 2007)
Abstract: In this paper we investigatc and build up three methods for transíorming sequential processes of a net system into concurrent oncs. These mcthods are based on: trace languages, shift- lcft and case graphs. They arc also prescnlcd by detail algonthms and can be applicd to other modcls of concurrcnt systems. Keywords: net system, reliance alphabet, trace language, maximal concurrent steps, case graph.